A screening test for oral cancer using saliva samples: Proteomic analysis of biomarkers in whole saliva. Issue 1 (January 2015) - Katakura, Akira; Yamamoto, Nobuharu; Sakuma, Takumi; Sugahara, Keisuke; Onda, Takeshi; Noguchi, Sunaki; Shibahara, Takahiko
Abstract Background We have been developing a screening test for oral cancer using whole saliva samples, which can be easily and noninvasively collected repeatedly. We have performed proteomic studies to comprehensively assess changes in protein expressions of whole saliva, revealing that some proteins are either expressed or unexpressed specifically in oral squamous cell carcinoma (OSCC). Methods Here, we employed two-dimensional electrophoresis (2-DE) and peptide-mass fingerprinting (PMF) to identify biomarkers that specifically change expression in OSCC. Results The results showed that ten protein spots were specific to the preoperative whole saliva of OSCC patients, but were absent in the whole saliva of healthy individuals and OSCC patients after surgery. Of these spots, detection of enolase 1 in the saliva was shown to be significantly higher for OSCC patients than for healthy individuals. Immunohistochemical staining confirmed that appearance of enolase 1 was significantly higher in OSCC tissue than in healthy tissue. Conclusion The above findings suggest the usefulness of enolase 1 as a salivary biomarker for OSCC, and this protein may be originated from OSCC tissue.